Artificial Intelligence in Psychological Qualitative Data Analysis: Is It a Balance Between Efficiency and Originality? - Rosemary , Chigevenga (International Journal of Qualitative Research, 2025)
Technological advancements have ushered in significant changes in the way activities are carried out across the world, including within the research domain. Artificial Intelligence (AI) tools are increasingly being applied to support a range of research tasks, such as data analysis. This has received both enthusiasm and skepticism. The purpose of this scoping review was to explore the benefits and drawbacks of using AI tools in analysing psychological qualitative data to establish if there is a balance between efficiency and human originality. Eight studies formed the sample, as there is limited research that utilised AI tools in analysing qualitative psychological data. Findings show that AI tools have the potential to make data analysis accurate, efficient, and scalable, improving behaviour prediction and giving nuanced and objective analysis. On the other hand, it was noted that these tools may perpetuate inherent biases, raise some ethical concerns, lack transparency, and may generate misinformation. To create a balance between efficiency and human originality, cognisance must be given to the fact that these tools must not come as a substitute for traditional qualitative analysis of psychological data, but must be used in a hybrid form of approach. Of importance, training data for these tools should always be updated to avoid bias and possible violation of human rights.